2019
DOI: 10.1021/acsami.9b07404
|View full text |Cite
|
Sign up to set email alerts
|

Simple and Multifunctional Natural Self-Assembled Sterols with Anticancer Activity-Mediated Supramolecular Photosensitizers for Enhanced Antitumor Photodynamic Therapy

Abstract: Supramolecular photosensitizers based on nanosized drug delivery or combination therapy have been proposed as a promising strategy for cancer treatment. Herein, we screen and develop a series of multifunctional single-component, carrier-based, natural small-molecule sterols (ergosterol, β-sitosterol, and stigmasterol) that simultaneously possess self-assembly ability, anticancer activity, and better biocompatibility and biodegradability to deliver photosensitizer chlorin e6 (Ce6) for significantly combined and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 50 publications
0
34
0
Order By: Relevance
“…14). 119 A UV-Vis spectrum analysis of the Ergo-Ce6 NPs conrmed the presence of p-p stacking and hydrophobic interactions and showed that the Ce6 molecules existed mainly as monomers between stacked ergosterol molecules. In water, the Ergo-Ce6 NPs showed a uorescence quenching efficiency of about 93.7% compared to the monomer Ce6, but the heat generation process was not promoted.…”
Section: Co-assembly Of Pdt and Cht Componentsmentioning
confidence: 99%
“…14). 119 A UV-Vis spectrum analysis of the Ergo-Ce6 NPs conrmed the presence of p-p stacking and hydrophobic interactions and showed that the Ce6 molecules existed mainly as monomers between stacked ergosterol molecules. In water, the Ergo-Ce6 NPs showed a uorescence quenching efficiency of about 93.7% compared to the monomer Ce6, but the heat generation process was not promoted.…”
Section: Co-assembly Of Pdt and Cht Componentsmentioning
confidence: 99%
“…The study of cellular uptake and in vitro cytotoxicity of cyclic arginine-glycine-aspartic and octa-arginine peptide-modified ergosterol-combined cisplatin liposomes showed their stability in serum and the strongest anti-lung cancer effect [ 39 ]. The encapsulation of chlorin e6 in self-assembled ergosterol nanoparticles resulted in a novel supramolecularly assembled photosensitizer [ 64 ]. When applied to cancer cells 4T1 and MCF-7, it showed remarkable in vitro phototoxicity with cell inhibition of about 73% and 92%, respectively.…”
Section: Sterolsmentioning
confidence: 99%
“…For the in vivo experiments, the anticancer efficiency of ergosterol/Ce6 nanoparticles can be as high as 86.4%, which is much higher than that of ergosterol nanoparticles (51.0%) or Ce6 PDT alone (59.5%). 59 Combined chemotherapy with PDT shows great potential for clinical application. While supramolecular assembly offers more possibilities for performing combined therapy.…”
Section: Pdt Based On Co-assemblymentioning
confidence: 99%
“…A) The co-assembled ergosterol/Ce6 nanoparticles can be used for combined antitumor therapy, depending on the anticancer activity of ergosterol, as well as the PDT from Ce6;59 (this figure has been reproduced from ref. 59 with permission from American Chemical Society).…”
mentioning
confidence: 99%